Plastic Waste Management as a Alternative Energy Source to Support Sustainable Development Goals and Environmental Ethics: A Systematic Literatur Review - Siti Fatimah; Aditya Marianti; Margareta Rahayuningsih (Universitas Hamzanwadi, 2024)
This research aims to analyze the management of plastic waste as an alternative energy source in supporting SGDs and forming environmental ethics through systematic literature review and bibliometric analysis. Trend analysis is used to determine the extent of research on plastic waste management from 2020 to 2023. Additionally, the study of environmental ethics is analyzed to understand the extent to which plastic waste can be utilized as an alternative energy source. This study utilizes Bibliometrix software with R programming and VOSviewer. Qualitative methods and techniques are adopted to review literature published from 2020 to 2023. Literature search was conducted in February-March 2024 through the Scopus database. The research was conducted using the keywords (plastic AND waste AND management AND energy), resulting in 1,035 documents from 2020 to 2023. Then, the obtained documents were filtered to include only those in English, at the final stage, and open access, resulting in 302 documents. Further analysis was conducted to assess their relevance to the research topic, resulting in 211 documents. The data were documented in (.csv) format and analyzed using VOSViewer and Biblioshiny applications. The research indicates that the trend in research on managing plastic waste as a renewable energy source has significantly increased. The majority of opportunities for plastic waste as an alternative energy source involve converting plastic waste into biogas. The management of plastic waste is one form of environmental ethics.